Clinical efficacy and safety of the superpulse thulium fiber laser and holmium laser for ureteroscopic lithotripsy in the treatment of upper urinary tract calculi: a randomized, positive control, blinded, single-center clinical study {1} - Cheng Pang; Weiwei Fang; Fanguo Zhang; Ming Liu (Trials)
Abstract Background Kidney stone disease is a common problem. The holmium: yttrium–aluminum–garnet (HO:YAG) laser is currently the gold standard laser for ureterorenoscopic (URS) lithotripsy. Recently, the superpulse thulium fiber laser (SP TFL) has shown potential as a substitute for the HO:YAG laser. We aim to compare and evaluate the clinical efficacy and safety of the HO:YAG laser and SP TFL in the treatment of upper urinary calculi in this trial. Methods In this randomized, positive control, blinded management, single-center clinical study, patients with upper urinary calculi will be randomized (1:1) to the experimental group (SP TFL group) or the control group (HO:YAG laser group). Patients in both groups will undergo URS lithotripsy under general anesthesia, and according to the results of randomization, the patients will be treated with an SP TFL (trial group) or a holmium laser (control group). The primary outcome is the stone-free rate at 30 ± 7 days after surgery. The secondary outcomes include the duration of surgery, the duration of laser use, the length of postoperative hospital stay, postoperative clinical indicators, total hospitalization costs, the second-stage stone clearance rate, perioperative complications, the average hemoglobin change, and the mean white blood cell count change. Discussion This study aims to evaluate and compare the clinical efficacy and safety of the SP TFL and HO:YAG for URS lithotripsy in the treatment of upper urinary calculi. Trial registration {2a and 2b} chictr.org.cn ChiCTR2300076893. Registered on October 24, 2023, with ChiCTR ( https://www.chictr.org.cn/bin/project/edit?pid=206827 ). Protocol version {3} August 15, 2023 (V.20230815).